THE IMPACT OF PARENTAL INVOLVEMENT AND PUBLIC RELATIONS MANAGEMENT PROGRAM ON THE QUALITY OF EDUCATION WITH COLLABORATION AS MEDIATION AT SDN CILEGON 4 - Maseliya, Maseliya; Sariwardani, Andriani; Dewi, Ratna (Cakrawala Pedagogik, 2025)
The purpose of this study was to determine the impact of parental involvement on the quality of education, the impact of public relations management programs on the quality of education, the impact of parental involvement and public relations management programs on the quality of education with collaboration as mediation. This study uses a qualitative method. Data collection was carried out using observation, in-depth interviews and documentation. The subjects of this study were several parents of students taken purposively, as well as the head of the SDN Cilegon 04 Committee, a representative of the community. The results of the study indicate that (1) parental involvement plays an important role in the quality of education such as actively assisting children to study at home, good communication with the school, and supporting school program activities, (2) Public relations management programs have a major impact on improving the quality of education. Effective public relations management can contribute to schools in creating positive relationships with the community, increasing parental involvement and strengthening the school's good name, (3) Public relations management is the most important part in connecting communication and collaboration between school residents, parents of students and the community so that there is no misinterpretation. Communication and collaboration are carried out both directly and indirectly